Results of wound healing of platelet-rich plasma gel from umbilical cord blood in experiment - Do, Thanh Hoa; Do, Xuan Hai (Tạp chí Y học Thảm hoạ và Bỏng, 2024)
Objective: To evaluate the wound healing effect of PRP gel from human umbilical cord blood in experimental studies.Subjects and methods: The extra-long dorsal skin flaps on 18 white rats were treated for wound healing by injecting PRP gel from human umbilical cord blood and the control was injected with 0.9% NaCl at a dose of 0.5 ml/injection point.Research results: the living area of the skin flaps injected with PRP gel from human umbilical cord blood on days 3; 7 and 14 were 4.1 ± 0.2, 3.9 ± 0.1 and 3.8 ± 0.1cm2, respectively, significantly different from the control group (p < 0.05). The average number of blood vessels and the average total blood vessel area increased over time when compared with the control group (p < 0.05).Conclusion: PRP gel from human umbilical cord blood stimulates angiogenesis and promotes wound healing in experimental studies.